Similar Diversity of Alphaproteobacteria and Nitrogenase Gene Amplicons on Two Related Sphagnum Mosses - Bragina, Anastasia; Maier, Stefanie; Berg, Christian; Müller, Henry; Chobot, Vladimir; Hadacek, Franz; Berg, Gabriele (Frontiers in Microbiology, 2012)
Sphagnum mosses represent a main component in ombrotrophic wetlands. They harbor a specific and diverse microbial community with essential functions for the host. To understand extend and degree of host specificity, Sphagnum fallax and S. angustifolium, two phylogenetically closely related species, which show distinct habitat preference with respect to the nutrient level, were analyzed by a multifaceted approach. Microbial fingerprints obtained by PCR-SSCP (single-strand conformation polymorphism) using universal, group-specific and functional primers were highly similar. Similarity was confirmed for colonization patterns obtained by fluorescence in situ hybridization (FISH) coupled with confocal laser scanning microscopy (CLSM): Alphaproteobacteria were the main colonizers inside the hyaline cells of Sphagnum leaves. A deeper survey of Alphaproteobacteria by 16S rRNA gene amplicon sequencing reveals a high diversity with Acidocella, Acidisphaera, Rhodopila and Phenylobacterium as major genera for both mosses. Pathogen defense and nitrogen fixation are important functions of Sphagnum-associated bacteria, which are fulfilled by microbial communities of both Sphagna in a similar way. NifH libraries of Sphagnum-associated microbial communities were characterized by high diversity and abundance of Alphaproteobacteria but contained also diverse amplicons of other taxa, e.g. Cyanobacteria, Geobacter and Spirochaeta. Statistically significant differences between the microbial communities of both Sphagnum species could not be discovered in any of the experimental approach. Our results show that the same close relationship, which exists between the physical, morphological and chemical characteristics of Sphagnum mosses and the ecology and function of bog ecosystems, also connects moss plantlets with their associated bacterial communities.